Analysis of Digital Transformation Strategy Opportunities and Threats of Food Stalls Small Medium Enterprises in the Industry 4.0 - Natasya Sikki; John Reimon Batmetan (International Journal of Information Technology and Education, 2022)
SMEs as a sector that has been proven to be able to survive in a crisis, therefore SMEs are encouraged to accelerate the digital transformation process in the era of the industrial revolution 4.0. This study aims to understand the importance of the right digital transformation for every MSME business. This study is a qualitative research through analysis of literature and other supporting data to produce a picture of the right digital transformation for SMEs. This research shows that digital transformation comes from external factors, not many internal factors that trigger digital transformation are found. The transformations carried out tend to follow the transformation steps that have been developed so that they do not create uniqueness. In the general implementation of digital transformation, SMEs have established a strategic imperative for them to carry out digital transformation, but have not implemented benchmarks so that the level of success of digital transformation cannot be measured.